P1_1 Laser Power - Evans, Daniel; Fox, Adam; Morland-Nuttall, Thomas; Bowes-Reynolds, John (Physics Special Topics, 2021)
The possibility of using a laser to provide power to a distant spacecraft via solar panels is examined. The power and divergence combinations of a laser required to outperform the Sun is determined at the distance of Pluto, a possible combination identified is a divergence of 3.5 × 10−6 rad, and a power of 260 TW. The results show that it would be possible however not recommended due to substantial inefficiency.